Pengaruh Interaksi Sosial Terhadap Motivasi Belajar Mahasiswa Baru Pendidikan IPA - Qotrunnada Firdaus; I Ketut Mahardika; Devi Aryanti; Imana Bellany Filianti; Sayu Sukma Sejati; Rizka Elan Fadillah; Firda Yusmar (Jurnal Ilmiah Wahana Pendidikan, 2022)
Education is an effort to prepare a human being to become an independent person, capable of being a useful part of the community and taking part in efforts to build the nation. The purpose of this study was to determine the effect of social interaction on the learning motivation of new science education students. This study uses a literature study approach. The targets in this study were new students of Science Education at the University of Jember. In analyzing the primary hypothesis we use an analysis of the literature study. Conclusion, namely: Based on the analysis that we have done, it can be seen that there is a positive and significant interaction between social interaction and the learning motivation of new students of the Science Education Study Program at the University of Jember